2019
DOI: 10.1101/871608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective buprenorphine use and tapering strategies: Endorsements and insights by people in recovery from opioid use disorder on a Reddit forum

Abstract: Opioid use disorder (OUD) is a national crisis in the United States and buprenorphine is one of the most effective evidence-based treatments. However, few studies have explored successful strategies for using and tapering buprenorphine to achieve stable recovery, particularly due to the difficulties of conducting long-term studies involving patients with OUD. In this study, we show that discussions on the anonymous social network Reddit may be leveraged, via automatic text mining methods, to discover successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although there are a growing number of studies that use NLP to look at existing posts on Reddit to answer research questions, there are few studies that use Reddit for surveys or as a recruitment tool. [32][33][34][35][36] Given the anonymity of Reddit and its large subscriber base, it could be a valuable source to survey questions about sensitive topics, perform toxicosurveillance, and study use patterns and adverse effects of emerging drugs with a novel method. 36 As new psychoactive substances emerge in the drug market, Reddit could be a promising resource to study these substances with the goal of informing public health, harm reduction efforts, and clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a growing number of studies that use NLP to look at existing posts on Reddit to answer research questions, there are few studies that use Reddit for surveys or as a recruitment tool. [32][33][34][35][36] Given the anonymity of Reddit and its large subscriber base, it could be a valuable source to survey questions about sensitive topics, perform toxicosurveillance, and study use patterns and adverse effects of emerging drugs with a novel method. 36 As new psychoactive substances emerge in the drug market, Reddit could be a promising resource to study these substances with the goal of informing public health, harm reduction efforts, and clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 This study adds to the body of literature focusing at the intersection of social media and OUD by using NLP to uncover discussions about a medical phenomenon, precipitated opioid withdrawal, associated with buprenorphine initiation after chronic fentanyl use. Similar to Graves et al (2019), this study draws from the experiences and voices of patients with OUD, often shared anonymously, to address evolving buprenorphine initiation strategies. 16 Our finding of multiple dosing regimens of buprenorphine microdosing (Table 3) is comparable to the multiple different dosing regimens described in case reports with a few exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Graves et al (2019), this study draws from the experiences and voices of patients with OUD, often shared anonymously, to address evolving buprenorphine initiation strategies. 16 Our finding of multiple dosing regimens of buprenorphine microdosing (Table 3) is comparable to the multiple different dosing regimens described in case reports with a few exceptions. 2,3,8,9 For example, the lowest dose described in our data started at 0.125 mg of buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including our own, have utilized social media to identify large cohorts of users with common health-related conditions, and then mine relevant longitudinal information about the cohorts using NLP methods. For example, in our past research, we showed that carefully-designed NLP pipelines can be used to discover cohorts of pregnant women [11] or patients suffering from opioid use disorder [6] from social media, and then mine important information from their social media posts ( e.g ., medication usage and recovery strategies). For cancer, studies have investigated the role of social media platforms for tasks such as spreading breast cancer awareness, health promotion, and cancer prevention [1, 3].…”
Section: Introductionmentioning
confidence: 99%